Effect of water regime and fertigation on yield and quality of sweet orange (Citrus sinensis Osbeck) cv. Mosambi in arid zone (Indian Journal of Arid Horticulture, 2025)
A field experiment was conducted on sweet orange (Citrus sinensis) to study the effect of water regime and fertigation on yield and quality at Precision Farming Development Centre, Agricultural Research Station, Swami Keshwanand Rajasthan Agricultural University, Bikaner. The experiment was laid out in split plot design with four replications and consisting twelve treatment combinations, comprised four water regime (0.6, 0.8 and 1.0 volume of water through drip irrigation and another one 1.0 volume of water applied by surface irrigation method) and three levels of recommended dose of NPK (75, 100 and 125%). The results indicated that maximum fruit diameter (7.36 cm), fruit yield (38.17 kg/plant), juice weight (100.4 g), peel weight (47.95 g), reducing sugar (2.33%) and total sugar (8.36%) were recorded in 1.0 volume of water through drip irrigation which was at par with 8.0 volume of water through drip irrigation and significantly superior over 0.6 volume of water. Whereas, maximum acidity (0.76%) was recorded in 0.6 volume of water through drip. Further data showed that among the RDF levels, fertigation with 125% RDF gave maximum fruit diameter (7.20 cm), fruit yield (32.48 kg/plant), juice weight (85.42 g), peel weight (41.59 g), reducing sugar (1.94%) and total sugar (7.63%) which was comparable with 100% RDF and significantly superior over 75% RDF. Whereas, maximum acidity (0.72%) was recorded in 75% RDF followed by 100% RDF and lowest in 125% RDF.
Keywords: Water regime; fertigation; fruit yield; reducing sugar; acidity; juice; RDF